Livestock Waste, Potential Manure Production and Its Use in Japan in 1980 and 2010. (15th December 2017) - Mishima, Shin-ichiro; Leon, Ai; Eguchi, Sadao; Shirato, Yasuhito
ABSTRACT: The aim of this work is to quantify life cycle of nutrient elements for soil and crops, namely nitrogen (N), phosphorus (P), potassium (K), and carbon (C), from feed of livestock to potential of manure production via livestock waste, a potentially sustainable application of manure for farmland soils in Japan in 1980 and 2010. We also estimated real application to farmland from a questionnaire by setting several hypotheses to collect real proportion of farm households, because the questionnaire was intended for full-time farms, the proportion of which is minor within all farms. The questionnaire survey was conducted five times, from 1979 to 2003 for 5-year intervals, and one time from 2008 to 2013. These data were set for the years 1980 and 2010. As a result, the livestock feed became lower in P and K input, livestock got better nutrient use efficiency for livestock products, and waste production was reduced in 2010 than 1980. Potential of manure production was decreased in 2010 from what it was in 1980; however, estimated application of manure was also reduced from full to half of potential of manure production. Application level of manure in 1980 was higher than the amount that farmland received sustainably. This might be allowed for enhancing soil fertility; as such activity was also needed at that time. On the other hand, in 2010, application of manure was estimated to be less than half of that in 1980 and had not reached sustainable application level. From 1980 to 2010, manure application had been decreased, even though trends of manure application for crops per area were different in each crop. Although lack or surplus of manure might not always explain trend of soil fertility, we need continues survey of soil fertilities to check and monitor to grasp the trend of soil fertility indicated by total C and N, available N, P, and K, as well as estimate application of manure to farmland.